Audit strategies to reduce hospital admissions for acute asthma. Issue 2 (August 1993) - Connett, G J; Warde, C; Wooler, E; Lenney, W
Abstract : An eightfold rise in hospital admissions for acute asthma from 1971-85 prompted two studies to audit the admissions policy at the Royal Alexandra Hospital. In the first study the on call senior house officer (SHO) was replaced by an experienced registrar and over a four month period 53 children out of 158 were sent home from the receiving room compared with six out of 39 seen by the SHOs. In the second study an SHO training programme was established together with a home treatment package. Over a 12 month period the on call SHOs assessed 687 children with acute asthma; 229 (43.5%) were deemed fit to be sent home. Only seven of these were readmitted within one week. Diary symptom score cards filled in by parents indicated that children sent home without admission fared no worse at home than those admitted and then discharged for the two weeks after leaving hospital. The development of strategies to improve assessment and immediate management in the hospital receiving room can reduce hospital admissions for acute asthma, allowing more children to be safely managed in the community.